Six Stroke Engine Arrangement - Maisara Mohyeldin, Gasim Mohamed (2012)
In six stroke engine, there are additional two strokes, namely another power and exhaust strokes. The engine works through harnessing wasted heat energy created by the fuel combustion. After the combustion stage water is injected into the super- heated cylinder. The water explodes into steam and force the piston down. It in turn helps to cool the engine. That resulted in normal levels of power but using much less fuel. It also has the advantage of not requiring an external cooling system. In order to achieve these benefits, major modifications of conventional internal combustion engine must be done. In this paper the modification of the conventional four stoke internal combustion engine is illustrated to convert it into six stroke engine.